Succeeding the Great Aeneas: ideological parallels of Augustan succession in the Aeneid and on the Ara Pacis - Stassen, Heidie (Stellenbosch : Stellenbosch University, 2024)
Thesis (MA)--Stellenbosch University, 2024.